Updated records and range expansion of alien marine macrophytes in Greece (2009) - TSIAMIS, K.; MONTESANTO, B.; PANAYOTIDIS, P.; KATSAROS, C.; VERLAQUE, M. (Mediterranean Marine Science, 2010)
In the present study the list of alien marine macrophytes already recorded on Greek coasts has been revised in the light of recent studies and new observations. In comparison to 2008, the total number consists of 32 taxa, and the classification as established, casual and debatable species has been modified, with a total of 14, 5 and 13 species respectively. An interesting increase in established species from 9 taxa in 2008 to 14 taxa in 2009 is noted. With 23 taxa listed, Rhodobionta is the best represented group, followed by Chlorobionta (4 taxa) and Chromobionta (4 taxa), while seagrasses (Streptobionta) are represented by only one species. Several new records, one new entry and two putative additions are considered here, while two other taxa previously assumed introduced are excluded from the list of aliens.